PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI TERHADAP KINERJA GURU DI SMP - Herman, Edi; Matsum, Junaidi H; Khosmas, F.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractÂ Overview of research on the influence of professional competence on teacher performance, the influence of work motivation on teacher performance and the influence of professional competence and work motivation on teacher performance. Using quantitative methods. With testing techniques using a Likert scale. Validity test uses the Pearson Product Moment formula with SPSS version 17.0 program, reliability test using Statistics Cronbach's Alpha. The results of the trial obtained reliability of Professional Competence is> 0.60 that is equal to 0.779, Motivation is> 0.60 that is equal to 0.756 and Performance> 0.60 is equal to 0.802. The results of data analysis (1) professional competence is high, (2) teacher's work motivation is high, and (3) teacher performance is also high. There is a significant relationship (1) between professional competence and teacher performance, with the overall value (42.20%) of respondents being a high competence category, (2) between work motivation and teacher performance, with a value of 43.0%, (3) between professional competence and work motivation together on teacher performance with a value of 0.487 or 48.7%. this means that between Professional Competence and Work Motivation together influence the Teacher's Performance. Â Keywords: Professional Competence, Motivation, Teacher Performance